2015
DOI: 10.9771/cmbio.v13i2.11693
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento epidemiológico de lesões orais potencialmente malignas em um centro de referência na Bahia

Abstract: <!--[if gte mso 9]><xml> <w:WordDocument> <w:View>Normal</w:View> <w:Zoom>0</w:Zoom> <w:TrackMoves /> <w:TrackFormatting /> <w:HyphenationZone>21</w:HyphenationZone> <w:PunctuationKerning /> <w:ValidateAgainstSchemas /> <w:SaveIfXMLInvalid>false</w:SaveIfXMLInvalid> <w:IgnoreMixedContent>false</w:IgnoreMixedContent> <w:AlwaysShowPlaceholderText>false</w:AlwaysShowPlaceholderText> <w:DoNotPromote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…Therefore, these results are in accordance with the scientific literature, especially regarding the age of the individuals, since the records reveal that 95% of cases of oral cavity cancer occurred in people aged 40 years or more, and that the average age at the time of diagnosis was during the sixth decade of life [3,[5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, these results are in accordance with the scientific literature, especially regarding the age of the individuals, since the records reveal that 95% of cases of oral cavity cancer occurred in people aged 40 years or more, and that the average age at the time of diagnosis was during the sixth decade of life [3,[5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 86%
“…Considering, specifically, the women, it has been observed that the majority of women involved in domestic activities present a higher incidence of oral cancer [5,17], possibly due to the same justification of income and lower educational level.…”
Section: Discussionmentioning
confidence: 99%